Ethical Appetite: The Market Dynamics of Price Premiums for Animal Welfare-Friendly Food Products - Nakavachara, Voraprapa; Thongtai, Chanon; Chalidabhongse, Thanarat; Pharino, Chanathip (Research on World Agricultural Economy, 2026)
This study examines the relationship between animal welfare standards labeled on packages and retail pricing using real-world data from a Swiss supermarket. This data collection, before the mandatory animal-based food labeling, helps provide a clean baseline that represents market prices unaffected by regulatory requirements by the Swiss government, which allows a genuine assessment of the observed existing price premiums. The front-of-package animal welfare scores range from 1 to 5, with 5 being the highest; the scores are available in categories of products where animal welfare is a relevant factor: Dairy & Eggs, Meat & Fish. On average, a one-point increase in the animal welfare score corresponds to a 16.0% price increase, with the effect most pronounced in Dairy & Eggs (24.2%) compared to Meat & Fish (14.7%). This premium likely reflects both consumer willingness to pay for an ethically aligned sustainable agri-food system and producer cost burdens associated with higher welfare standards. Broader cultural and educational contexts in Switzerland may further reinforce societal acceptance of animal welfare practices. Our findings contribute to the understanding of how market, production, and cultural factors interact, offering insight into how ethical attributes are reflected in retail food pricing, as well as sustainable development goals (SDGs). ER